ESTIMATION OF ENTRANCE SKIN DOSE IN ANALOGUE X-RAY FACILITIES OF SOUTHERN DELTA STATE, NIGERIA: A MATHEMATICAL APPROACH TO RADIOLOGICAL PROTECTION - Akpolile, Anita F.; Ukerun-Akpesiri, Amanda A.; Eki, Crownbirth E.; Abdul, Francisca E. (FUDMA Journal of Sciences, 2026)
Radiation dose optimisation in diagnostic radiography is essential for patient safety and adherence to international standards. In many developing regions, analogue X-ray systems remain in use, raising concerns about elevated exposure levels. This study evaluated entrance skin dose (ESD) and effective dose in four government-owned hospitals in southern Delta State, Nigeria, all operating analogue X-ray equipment. Patient examinations included three routine projections: chest (AP), pelvis (SV), and abdomen (LS). The mean ESD values obtained were BGH1 (1.04 mGy), BGH2 (0.94 mGy), DEXC1 (1.78 mGy), and DEXC2 (0.87 mGy). These values exceeded the international diagnostic reference level of 0.4 mGy, though they were lower than those reported in several previous studies and marginally higher than results published by the same authors elsewhere. The elevated doses may reflect suboptimal operator techniques and inadequate equipment maintenance. Although quality control assessments are mandated quarterly, inconsistent compliance likely contributes to the observed deviations. The findings emphasize the need for stricter enforcement of quality assurance protocols and enhanced operator training to reduce patient radiation exposure. While the recorded doses remain within diagnostic ranges, optimization of radiographic practice is imperative to align with international benchmarks and safeguard patient health.